Characteristics of Multicomponent Interventions to Treat Childhood Overweight and Obesity in Extremely Cold Climates: A Systematic Review of a Randomized Controlled Trial - Albornoz Guerrero, Javier Hernan; Garcia, Sonia; Perez de Sevilla, Guillermo Garcia; Cigarroa, Igor; Zapata-Lamana, Rafael (My University, 2021)
Aim: To analyze the characteristics of multicomponent interventions to reduce childhood overweight and obesity in territories with an extremely cold climate. Methods: A systematic review was conducted following the PRISMA statement. MEDLINE, PsycNet, SciELO, and grey literature databases were reviewed in the period between 2010 and 2020. Results: 29 articles were included (n = 4434 participants; 9.3 years; 56% women) with an average adherence of 86%, 100% being the highest adherence, for the physical activity and nutrition interventions. The primary variables studied were BMI, BMI Z-score BMI-SDS and, additionally, the secondary variables studied were nutritional status and physical and mental health. In 72% of the interventions presented, positive effects were seen on the reduction of BMI, including in parents and their children. The interventions were carried out mainly by nutritionists in health centers. The duration of the 29 interventions was <= 6 months and >= 12 months, in 59% and 41% of the studies, respectively. 57% of the studies reported post-intervention results. 86% of the interventions included a physical activity component, 80% included a nutrition component, 66% included a behavioral therapy component and 55% included an education component. Concerning the effects of the intervention on the primary outcome, in interventions with a duration equal to or less than six months, the most effective interventions included recreational activities, education, and nutritional programs. In interventions lasting 12 months or more, the most effective interventions included physical activity recommendations, nutritional and physical exercise programs, and cooking classes. Conclusions: This systematic review analyzed the effectiveness of, and characterized, multicomponent interventions lasting for 6 and 12 months, aiming to treat childhood obesity in extremely cold climates. The most frequently used units of measurement were also analyzed and summarized. Evidence derived from RCT. These results can be useful for designing future interventions to treat childhood obesity in territories with an extremely cold climate.
Keywords: pediatric obesity; obesity management; treatment; extremely cold climate